The etiology of extensive pleural effusions with troublesome clinical course among children - Cirino, Luís Marcelo Inaco (2004)
CONTEXT: In São Paulo, pneumonia is the main infectious cause of death among children. Parapneumonic pleural effusion is a possible complication and has to be treated surgically when the patient does not respond to antibiotics. OBJECTIVE: Assessment of the etiology of complicated parapneumonic pleural effusions that needed surgical intervention. TYPE OF STUDY: Retrospective study. SETTING: University hospital of the University of São Paulo. METHOD: Analysis of 4,000 files on children hospitalized with pneumonia from November 1986 to November 1996 had shown that 115 of these children presented a total of 117 cases of pleural empyema that required surgical procedures. The children’s clinical condition was assessed in relation to radiological findings and to their nutrition and immunization status. Previous antimicrobial therapy and pleural effusion bacterioscopy were also evaluated. RESULTS: Streptococcus pneumoniae was the agent found most commonly, as frequently in blood cultures as in pleural effusions. DISCUSSION: Data on vaccination coverage, birth weight and nutritional status are analyzed and compared to other publications. We observed that pleural effusion has a high potential for discomfort, and in most cases it is not a complication of the first pulmonary disease episode. Previous use of antibiotics interfered with culture positivity. The agent most frequently found was Streptococcus pneumoniae, which is in accordance with the findings from other authors. Nonetheless, the antibiotics used to treat the patients after the procedure were the same used in non-complicated pneumonias, which has led us to conclude that the worse outcome in this cases was not due to drug resistance. CONCLUSION: The bacteriological profile in our series of complicated pneumonia cases was similar to what has been described for non-complicated pneumonia cases. Future studies will be necessary to determine why these children presented a worse outcome.